Combustion characteristics and NOx emissions of a waste cooking oil biodiesel blend in a marine auxiliary diesel engine. (25th March 2017) - Geng, Peng; Mao, Hongjun; Zhang, Yanjie; Wei, Lijiang; You, Kun; Ju, Ji; Chen, Tingkai
Graphical abstract: Highlights: Higher waste cooking oil biodiesel-diesel blends were applied in the marine auxiliary diesel engine. Effects of the test fuels on combustion and emissions clearly depends on engine conditions. Higher waste cooking oil biodiesel-diesel blends increase the cylinder pressure slightly, while decrease the ignition delay. Higher waste cooking oil biodiesel-diesel blends have potential for reducing the NOx emissions. The ratio of NO2 /NO decreases with the increase of the engine loads and biodiesel content in the test fuels. Abstract: The International Maritime Organization (IMO) has enacted the Maritime Agreement Regarding Oil Pollution (MARPOL) VI to regulate the ship emissions. In the large ocean-going ship, the marine auxiliary diesel engine is widely used to produce electricity, and it could also generate large amounts of harmful emissions. In order to reduce these emissions, some alternative fuels were used in the marine diesel engine. In term of this, the combustion and emissions characteristics and emissions of a 6-cyclinder turbocharged inter-cooling direct-injection marine auxiliary diesel engine was investigated in this study when using Ultralow Sulfur Diesel (ULSD), B70 (diesel containing 70 vol.% of biodiesel), B90 and neat waste cooking oil biodiesel (B100), respectively. The influence of high biodiesel to diesel ratio on the combustion characteristics and NOx (NO and NO2 ) emissions was studied, under 25%, 50%, 75% engine load at 1050 r/min and 1500 r/min (Rated speed) conditions. The experimental results indicated that the cylinder pressure decreases slightly with increasing the biodiesel content in the test fuels, while the ignition advances, ignition delay reduces and combustion duration becomes longer. When the test engine operated at low load, the maximum percent peak heat release rate (HRR) decreases is about 14.3%, while the maximum percent can reach to 21.3% at high load condition. For each test fuel, the cylinder pressure and peak heat release rate increase significantly with the increase of engine load. The temperature of the exhaust manifold decreases with the increases of biodiesel content in the test fuels. Moreover, the NOx emissions decrease significantly when using the high substitution ratio of biodiesel, which is due to the decrease of the cylinder temperature in the diffusion combustion mode. The NO emission increases with the increases of the engine torque, while the NO2 emission decreases. Consequently, the ratio of NO2 to NO decreases sharply with the increases of engine load, due to the increase of the cylinder temperature.